Another Cry of Heresy at Oxford: the Case of Dr John Holand, 1416 - Logan, F. Donald (Studies in church history, 1969)
The legal historian can scarcely help but encounter the world of academic learning in his studies. He meets the university teachers among his auctores; he finds the mode of their writing often determined by university exercises; in court records and formulary books he encounters graduates holding offices in the courts; he even finds the occasional wayward student who because of his impecunious ways or his transgression of the peace has been cited to appear in court. It is from a formulary book that a case of more than passing interest has come to light concerning Oxford in the early fifteenth century.